Near field control for enhanced photovoltaic performance and photostability in perovskite solar cells. (November 2021) - Hossain, Mohammad Ismail; Shahiduzzaman, Md.; Ahmed, Safayet; Huqe, Md. Rashedul; Qarony, Wayesh; Saleque, Ahmed Mortuza; Akhtaruzzaman, Md.; Knipp, Dietmar; Tsang, Yuen Hong; Taima, Tetsuya; Zapien, Juan Antonio
Abstract: We present a strategy for photon management in front contact of perovskite solar cells (PSCs) compatible with tandem and flexible PSCs capable of optimizing device characteristics while providing an additional mechanism to overcome excessive focusing that affects the device's photostability. Rigorous validation of the numerical modeling used was performed by fabricating PSCs in a superstrate configuration optimized to reach high performance, ECE = 17.4%, VOC = 1.02 V, JSC = 22.3 mA/cm 2, and FF = 77%. These 3D electromagnetic simulations combining the finite-difference time-domain (FDTD) and finite element method (FEM) techniques provide detailed insights of the photonic and electrical effects in PSCs. Numerical optimization of the dual capabilities of a novel nanostructured front contact enables control of the absorbed power density distribution to maximize efficiency while simultaneously minimizing nanostructure-related sub-wavelength focusing effects. In-depth analysis of the proposed photon management reveals enhanced electrical characteristics to maximize charge extraction leading to JSC enhancements of ~15 that can be as high as 33% for ultra-thin active layers suitable for flexible PSCs compared to planar PSCs performance. Furthermore, we show that the design of the front contact layer's nanostructure enables control of the power density distribution in the device to engineer PSCs' photostability without compromising performance enhancements afforded by the nanophotonic front contact. Details of the nanophotonic front contact, device, and fabrication process are provided. Graphical Abstract: ga1 Highlights: The front contact integrated with hybrid nanoholes is designed for efficient perovskite solar cells (PSCs). Demonstrates the ability to modulate the illumination for high efficiency and better photostability of PSCs. Optoelectronic device modeling and performance, including photonic response, were investigated by 3D Multiphysics approach. Validation of the Multiphysics approach against high-quality PSC's detailed experimental data is conducted. The proposed nanophotonic device allows enhancing JSC and ECE by 15~33% and 30%, respectively, compared to the reference device.